The Legal Role and Responsibility of Thesis Supervisors About Student Final Project Plagiarism - Miftah Ulumudin Tsani; Dedi Sugiyanto; Cantika Aulia Febriyanti; Farah Mutia Yulianti (Scholar Center, 2024)
The problem of plagiarism in the academic environment is currently one of the problems that must be anticipated, technological developments have 2 conflicting impacts on students and lecturers, technology provides openness to all the information needed so that it can produce something positive if used and utilized properly but on the contrary, it will have a negative impact if misused in making scientific works. So that the Role and Legal Responsibility of Thesis Supervisors Against Plagiarism of Students' Final Assignments is deemed necessary to be studied, in this research article raises the formulation of the problem in the form of how the legal responsibility of the thesis supervisor to students who are proven to have committed plagiarism. The research method used is normative legal research, namely legal research that uses secondary data sources or data obtained through library materials in the form of laws and regulations, books or scientific research results. The results of this study are the responsibility of the thesis supervisor for plagiarism of students' final assignments regulated in the Regulation of the Minister of Education, Culture, Research and Technology Number 53 of 2023 concerning Quality Assurance of Higher Education and Law Number 28 of 2014 concerning Copyright. If a student's final assignment is proven to be plagiarized, legally the thesis supervisor is not held responsible. Still, there is an exception if the final assignment is developed into an article published in a scientific journal and includes the supervisor's name. The lecturer has violated academic integrity and must be held legally responsible in the form of administrative, civil and criminal cases.